2012
DOI: 10.1039/c2cp40278e
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces of ionic liquids and transition metal surfaces—adsorption, growth, and thermal reactions of ultrathin [C1C1Im][Tf2N] films on metallic and oxidised Ni(111) surfaces

Abstract: Ultrathin films of the ionic liquid 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C(1)C(1)Im][Tf(2)N]) were deposited on differently terminated Ni(111) single crystal surfaces. The initial wetting behaviour, the growth characteristics, the molecular arrangement at the interface, and thermal reactivity were investigated using angle-resolved X-ray photoelectron spectroscopy (ARXPS). On clean Ni(111), the initial growth occurs in a layer-by-layer mode. At submonolayer coverages up to at least 0.40 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(193 citation statements)
references
References 80 publications
(111 reference statements)
10
183
0
Order By: Relevance
“…7b. Starting at 0.55 monolayers, a transition to a checkerboard-type ''sandwich'' structure is found, with alternating orientations of neighboring sandwiches [156]; see Fig. 7c.…”
Section: Ionic Liquids In Catalysis 391mentioning
confidence: 96%
See 3 more Smart Citations
“…7b. Starting at 0.55 monolayers, a transition to a checkerboard-type ''sandwich'' structure is found, with alternating orientations of neighboring sandwiches [156]; see Fig. 7c.…”
Section: Ionic Liquids In Catalysis 391mentioning
confidence: 96%
“…PVD and ESID preparation methods enable the application of UHV-based analysis techniques now also for studying the IL/support interface under well-defined conditions, which is of highest relevance of SCILL applications. The first studies by AR-XPS demonstrated that the adsorption and wetting behaviour strongly depend on the particular combination of IL and support, with a strong influence of contaminations [150,156,192]. Furthermore, it was demonstrated that XPS can be also used to study reactions in ILs or at ILsubstrate or IL-electrode interfaces in situ, as a function of time or temperature [148,161,162,173,[193][194][195][196][197][198][199][200].…”
Section: Molecular Insights Into Il/gas and Il/support Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…[67][68][69][70][71][72] We also exclude studies where the reaction was not carried out in situ, that is, spectra were not recorded while the reaction proceeded, or the sample was moved to a different site in the XPS setup or was even removed from the XPS setup in order to carry out the reaction. [73][74][75][76][77] We also do not address studies that incorporate electrochemical sample manipulation, 66,67,[69][70][71][78][79][80][81][82][83][84][85][86] electrodeposition of metal or organic layers from ILs, [87][88][89][90][91] and IL decomposition 84,[92][93][94][95][96][97][98][99][100][101][102] or nanoparticle formation in ILs. 62,75,103 Each of these topics was studied extensively and would justify a separate review.…”
Section: Introductionmentioning
confidence: 99%